Pengaruh Model Pembelajaran Inquiry Berbantuan Media Torso Terhadap Hasil Belajar IPAS Kelas V SDN 101906 Pagar Jati Lubuk Pakam - Dosma Sinaga; Dyan Wulan Sari HS; Heka Maya Sari; Reflina Sinaga; Irmina Pinem (Journal on Education, 2024)
This research is an experimental research which aims to find out the inquiry learning model on student learning outcomes. This research was conducted at SDN 101906 Pagar Jati. This research method is the Pre-Exprimental Design experimental method by providing pretests, posttests and questionnaires. The results of statistical calculations show that learning outcomes increase by using the inquiry learning model in the very good category with an average score of 82,24, whereas without using the inquiry learning model it is included in the failure category with an average score of 49,76. It is said to have increased as evidenced by the results of the correlation coefficient calculation of 0,852, meaning r_(hitung ) (0,852) ≥ r_(tabel ) (0,396). Therefore, there is a strong influence of the Inquiry learning model on learning outcomes. Judging from the t test, it is 7,821 ≥ 2,069 thus Ha is accepted and Ho is rejected. This shows that there is a significant positive influence of the use of the inquiry learning model on the learning outcomes of class V students at SDN 101906 Pagar Jati Lubuk Pakam for the 2023/2024 academic year.